Comparison of the Transcriptomes of Long-Term Label Retaining-Cells and Control Cells Microdissected from Mammary Epithelium: An Initial Study to Characterize Potential Stem/Progenitor Cells - Choudhary, Ratan K.; Li, Robert; Evock-Clover, Christina M.; Capuco, Anthony V. (Frontiers in Oncology, 2013)
Background: Previous molecular characterizations of mammary stem cells (MaSC) have utilized fluorescence-activated cell sorting or in vitro cultivation of cells from enzymatically dissociated tissue to enrich for MaSC. These approaches result in the loss of all histological information pertaining to the in vivo locale of MaSC and progenitor cells. Instead, we used laser microdissection to excise putative progenitor cells and control cells from their in situ locations in cryosections and characterized the molecular properties of these cells. MaSC/progenitor cells were identified based on their ability to retain bromodeoxyuridine for an extended period. Results: We isolated four categories of cells from mammary epithelium of female calves: bromodeoxyuridine label retaining epithelial cells (LREC) from basal (LRECb) and embedded layers (LRECe), and epithelial control cells from basal and embedded layers. Enriched expression of genes in LRECb were associated with stem cell attributes and identified WNT, TGF-β and MAPK pathways of self renewal and proliferation. Genes expressed in LRECe revealed retention of some stem-like properties along with up-regulation of differentiation factors. Conclusions: Our data suggest that LREC in the basal epithelial layer are enriched for MaSC, as these cells showed increased expression of genes that reflect stem cell attributes; whereas LREC in suprabasal epithelial layers are enriched for more committed progenitor cells, expressing some genes that are associated with stem cell attributes along with those indicative of cell differentiation. Our results support the use of DNA-label retention to identify MaSC and also provide a molecular profile and novel candidate markers for these cells. Insights into the biology of stem cells will be gained by confirmation and characterization of candidate MaSC markers identified in this study.